Introduction: Critical Prison Studies, Carceral Ethnography, and Human Rights: From Lived Experience to Global Action - Sarah Turnbull; Joane Martel; Debra Parkes; Dawn Moore (Oñati Socio-Legal Series)
This collection of essays grew out of the workshop Critical Prison Studies, Carceral Ethnography, and Human Rights: From Lived Experience to Global Action held at the International Institute for the Sociology of Law (Oñati, Spain) in June 2016. The papers explore some of the challenges and possibilities of critical prison research, ranging from issues arising in university research ethics reviews to the limitations of penal reform efforts to end the practice of solitary confinement. Each essay is embedded in a different penal context: Australia, Italy, Russia, Canada, and the United States; and each contributes to broader discussions of critical prison research, utilizing new and old methods and sources, including the ‘netnography’ of prisoner websites and the archives of anti-carceral feminist campaigners. Collectively, the essays bring new insights and methods into scholarly and activist conversations aimed at understanding and responding to the harms of incarceration.